Validade de construção em testes de equilíbrio: Ordenação cronológica na apresentação das tarefas - Silveira, Carolina Rodrigues Alves [UNESP]; Menuchi, Marcos Rodrigo Trindade Pinheiro [UNESP]; Simões, Carolina Sant'Ana [UNESP]; Caetano, Maria Joana Duarte [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (My University, 2006)
The equilibrium tests of the Rosa Neto1 Motor Development Scale are constituted by ten tasks related to the chronological ages from 2 to 11 years and they determine the participants Motor Age. The tests presentation order is crescent from the child chronological age and the motor age is based on the success or failure in each task. The aim of this study was to analyze the construction validity of the equilibrium motor tests observing the ordering the levels of task difficulty. 76 children with 6 to 9 years of chronological age participated and were assigned in two groups: control group, tests presentation in increased order; and inverted group, tests presentation in decreased order. The results did not revealed statistical significant differences between groups, which indicate that the presentation order of the tests did not interfere in the children performance, independently of the chronological age. Low success rates occurred in some specific tasks followed by success in advanced tasks. As the results revealed that the participants could perform the tasks after that in which the failure happened the motor age ascribed by the Motor Development Scale can underestimate the children motor development. The variation of the children performance in the tasks suggests that the motor development process is nonlinear. The equilibrium motor tasks purposed in the Motor Development Scale show construction validity.
Construction validity in equilibrium tests: Chronological order in tasks presentation
Keywords: Evaluation; Psychomotor; Validity of test